Fast‐transient high‐performance 0.18 μm CMOS LDO for battery‐powered systems. Issue 8 (1st April 2017) - Pérez‐Bailón, J.; Márquez, A.; Calvo, B.; Medrano, N.; Martínez, P.A.
Abstract : A low‐power 0.18 µm CMOS capacitor‐less low‐dropout voltage regulator for battery‐operated portable devices is presented. A high‐gain telescopic cascode‐compensated amplifier is used to attain a stable topology with good static performances, while a very simple dynamic biasing circuit significantly enhances transient performances with no quiescent current penalty. Post‐layout results show a 1.8 V output voltage from a 3.6 to 1.9 V battery input voltage, delivering a 50 mA load current over a 100 pF load. The quiescent current is only 7 µA, the line and load regulations are, respectively, 0.039 mV/V and 0.17 mV/mA, and settling times are lower than 3.9 µs at full load transient.